Self-efficacy of physical education students in sports psychology learning - Yahya Eko Nopiyanto; Septian Raibowo; Andika Prabowo; Defliyanto Defliyanto; Ibrahim Ibrahim (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2022)
There are still physical education students who are unsure of their ability to participate in sports psychology learning. Based on this, the purpose of this study was to determine the level of self-efficacy of physical education students in attending sports psychology learning. The method used is the descriptive research method. The population used was 26 students. The total sampling technique was used to take the size of the research sample. The research techniques and instruments used were in the form of a questionnaire with a validity value of 0.72 and a reliability of 0.73. The mean ideal and standard ideal deviation are used to determine the category, and the percentage is used to determine the percentage of students. The results of the study stated that: 1) male students had a mean score of 51.11 and a standard deviation of 6.67 in the high category; 2) female male students have a mean value of 51.33 and a standard deviation of 6.83 in the high category. So it can be concluded that the level of self-efficacy is in the high category with a frequency of 20 students or 76%, and there is no difference between male and female students.